2010
DOI: 10.1007/s00228-010-0800-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of non-specific intravenous human immunoglobulins in Spanish hospitals; need for a hospital protocol

Abstract: IVIG is prescribed for a significant number of non-authorised and non-accepted indications with a notable cost. There is an important variability in IVIG prescriptions between hospitals, indicating room for improvement in IVIG use and the need for a consensus of protocol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 32 publications
3
35
1
Order By: Relevance
“…Adult studies have demonstrated that only 60–70% of IVIG prescriptions are used for FDA‐approved indications. Approximately, one‐third of the remaining indications were off‐label prescriptions according to the FDA or local guidelines with little scientific evidential support . However, little is known about IVIG prescriptions in the paediatric population.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…Adult studies have demonstrated that only 60–70% of IVIG prescriptions are used for FDA‐approved indications. Approximately, one‐third of the remaining indications were off‐label prescriptions according to the FDA or local guidelines with little scientific evidential support . However, little is known about IVIG prescriptions in the paediatric population.…”
contrasting
confidence: 68%
“…This figure is higher than the reported studies in adult and paediatric populations, which ranged between 42–58% . However, if approved off‐label indications such as Guillain Barre syndrome and dermatomyositis were included, then proportions of ‘approved’ indications were higher (more than 60%) …”
Section: Discussionmentioning
confidence: 60%
“…These indications currently represent 20 to 60% of the use of Ig. (2) It is important to point out that Ig can be used as a replacement therapy (Figure 1) or as immunomodulatory and anti-inflammatory agents (Figures 2 & 3). …”
Section: Introductionmentioning
confidence: 99%
“…In Spain, only some indications for the use of IVIGs have been authorized by the Spanish Medicines Agency on the basis of contributed evidence 9 . The authorized indications include replacement therapy and the subindications primary immunodeficiency (PID), secondary immunodeficiency (SID), and congenital AIDS in children (treatment of recurrent infections).…”
mentioning
confidence: 99%
“…A third authorized indication is allogeneic bone marrow transplantation. Within Spain, IVIGs are also used for a number of conditions not included in regulatory approvals and as a consequence are used off‐label with or without clinical scientific evidence supporting their use 1 , 9 …”
mentioning
confidence: 99%